Bimbingan Kelompok dengan Teknik Role Playing untuk Meningkatkan Self-Efficacy dan Harapan Hasil (Outcome Expectations) Karir Siswa - Ana, Aliqol; Wibowo, Mungin Eddy; Wagimin, Wagimin (Jurnal Bimbingan Konseling, 2017)
Penelitian ini dimaksudkan untuk menguji efek bimbingan kelompok dengan teknik role playing terhadap self efficacy dan outcome expectations. Jenis penelitian quasi eksprerimental dengan design pre-test post-test control group design diaplikasikan melibatkan 20 siswa yang memiliki skor total dari self-efficacy dan harapan hasil rendah yang dibagi menjadi kelompok eksperimen berjumlah 10 siswa dan kelompok kontrol berjumlah 10 siswa. Hasil penelitian menunjukkan bahwa penerapan bimbingan kelompok teknik role playing efektif untuk meningkatan self-efficacy karir dan harapan hasil (outcome expectation) siswa. Pembahasan dan saran terkait hasil penelitian ini dikaji dalam artikel ini.This research was intended to test the effect of group guidance service with role playing technique on students’ self efficacy and outcome expectation. A design of pre-test and post-test control group design was implemented with involving 20 students who have a total score of self-efficacy and low outcome expectations. They were divided two groups, namely: the experimental group of 10 students and control groups of 10 students. The data analysis technique used was MANOVA test with significance level of 5%. The results showed thatthe implementation of group counseling techniques by using role playing was effective in improving the students’ career self-efficacy and their outcome expectations. Discussion and recommendation based on thi findings were presented in this study.